Evaluation on the Practice and Behaviour of Women Applied for Gynecology Outpatient Clinics About Screening Methods for Early Diagnosis of Breast Cancer - AKDENİZ, ESRA (AVES, 2017)
Objective: Breast self-examination (BSE), clinical breast exam (CBE), mammography and ultrasound imaging (UI) are screening methods used for early diagnosis of breast cancer (BC). The purpose of this study is to put forth the utilization frequency of these screening methods among women presenting to the gynecology outpatient clinics and the relation of these data with the socio-demographic characteristics of the women. Materials and Methods: A survey was conducted among 429 women (age, 16-80 years) who were admitted to the gynecology outpatient clinics. The survey inquired about the rate and frequency of the performance of BSE, CBE, mammography and UI; personal and family history of breast cancer and social-demographic characteristics of the women. Results: The mean age was 40.08 (SD: 3.67). More than half of the women above 40 years of age (59.7 %) had never undergone mammography. 99.8 % of the women who had undergone mammography had also received ultrasound imaging. A significant relationship was identified between the BSE performance and having mammography. 57.4% of the women above 40 years of age (117) had UI, 53.9% (110) had CBE and 57.3% (117) performed BSE. There was a significant relationship between the age, education status and regular BSE; positive family history of BC and having CBE and mammography. Conclusion: The results reveal that the rate of BSE performance, having mammography and CBE are at less-than-ideal levels. In this context, it is apparent that breast cancer screening methods are needed to be introduced and guidance about their application frequency should be provided for women in gynecology outpatient clinics.
Keywords: Breast cancer; mammography; breast self-exam; clinical breast exam; ultrasound imaging; SELF-EXAMINATION; KNOWLEDGE; MORTALITY; MAMMOGRAPHY; AWARENESS; PROGRAM; EUROPE